Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.

pH-responsive “supra-amphiphilic” nanoparticles based on homoarginine polypeptides - Praveen, Korra; Das, Soumen; Dhaware, Vinita; Pandey, Bhawana; Mondal, Basudeb; Sengupta, Sayam (ACS Applied Bio Materials, 2019)
pH-responsive “supra-amphiphiles” based on double hydrophilic, positively charged block copolypeptides such as PEG-b-poly-l-lysine together with low molecular weight stimuli-sensitive partners that contain phosphate and carboxylate groups have been widely studied. In contrast, the other widely used cationic polypeptide poly-l-arginine whose cell-penetrating properties are well-known has been much less explored for the synthesis of supra-amphiphile-based nanomaterials. It is also known that the guanidine side chain of arginine binds to carboxylate anions with binding constants that are 2.5 times higher than the corresponding amines of poly-l-lysine. Here, we demonstrate the fabrication of pH-sensitive supra-amphiphilic nanoparticles by simple mixing of PEG2k-b-poly(homoarginine) block copolymer and carboxylic acid containing functional low molecular weight organic compounds. A high yielding three-step methodology was developed for the synthesis of ε-N,N′-di-Boc-l-homoarginine-α-N-carboxyanhydride which was polymerized using amine-terminated PEG (2000 MW) to yield 100% guanine-functionalized polypeptide (PEG2k-b-PHR30) with controlled molecular weights and low PDIs. Incubation of PEG2k-b-PHR30 with four different carboxylic acids (including dexamethasone a glucocorticoid receptor used in cancer therapy) in water leads to the formation of “supra-amphiphilic” nanoparticles (<200 nm size) due to the charge neutralization resulting from the strong interaction between the guanidine group and the carboxylate group. All these nanoparticles were able to encapsulate the hydrophobic dye Nile red with varying efficiency. Although these assemblies were stable at neutral pH, upon lowering the pH of the solution between 4 and 5, the protonation of the carboxylic acids leads to disassembly of these nanoparticles. The cytotoxicity of all four “supra-amphiphilic” nanoparticles varied depending on the carboxylic acid used for their fabrication. While the nanoparticle formed using dioctylbenzoic acid displayed 80% cell viability at concentration of 60 μg/mL, those formed with the steroid deoxycholic acid or dexamethasone showed only 40% cell viability at similar concentrations. Colocalization studies performed using epifluorescence microscopy demonstrate the successful uptake of intact dye-encapsulated nanoparticle inside the cell.

Amphiphilic mannose-6-phosphate glycopolypeptide-based bioactive and responsive self-assembled nanostructures for controlled and targeted lysosomal cargo delivery - Mondal, Basudeb; Pandey, Bhawana; Parekh, Nimisha; Panda, Sidharth; Dutta, Tahiti; Padhy, Abinash; Sen Gupta, Sayam (Biomaterials Science, 2020)
Receptors of carbohydrate mannose-6-phosphate (M6P) are overexpressed in specific cancer cells (such as breast cancer) and are also involved in the trafficking of mannose-6-phosphate labeled proteins exclusively onto lysosomes via cell surface M6P receptor (CI-MPR) mediated endocytosis. Herein, for the first time, mannose-6-phosphate glycopolypeptide ((M6P)GP)-based bioactive and stimuli-responsive nanocarriers are reported. They are selectively taken up via receptor-mediated endocytosis, and trafficked to lysosomes where they are subsequently degraded by pH or enzymes, leading to the release of the cargo inside the lysosomes. Two different amphiphilic M6P block copolymers (M6P)GP(15)-(PPO44)-P-A and (M6P)GP(15)-(PCL25)(2) were synthesized by click reaction of the alkyne end-functionalized (M6P)GP(15) with pH-responsive biocompatible azide end-functionalized acetal PPO and azide end-functionalized branched PCL, respectively. In water, the amphiphilic M6P-glycopolypeptide block copolymers self-assembled into micellar nanostructures, as was evidenced by DLS, TEM, AFM, and fluorescence spectroscopy techniques. These micellar systems were competent to encapsulate the hydrophobic dye rhodamine-B-octadecyl ester, which was used as the model drug. They were stable at physiological pH but were found to disassemble at acidic pH (for (M6P)GP(15)-(PPO44)-P-A) or in the presence of esterase (for (M6P)GP(15)-(PCL25)(2)). These (M6P)GP based micellar nanoparticles can selectively target lysosomes in cancerous cells such as MCF-7 and MDA-MB-231. Finally, we demonstrate the clathrin-mediated endocytic pathway of the native FL-(M6P)GP polymer and RBOE loaded (M6P)GP micellar-nanocarriers, and selective trafficking of MCF-7 and MDA-MB-231 breast cancer cell lysosomes, demonstrating their potential applicability toward receptor-mediated lysosomal cargo delivery.

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly

Copper(II) import and reduction are dependent on His-Met clusters in the extracellular amino terminus of human copper transporter-1 - Kar, Sumanta; Sen, Samarpita; Maji, Saptarshi; Saraf, Deepashri; Ruturaj; Paul, Rupam; Dutt, Sohini; Mondal, Basudeb; Rodriguez-Boulan, Enrique; Schreiner, Ryan; Sengupta, Durba; Gupta, Arnab (Journal of Biological Chemistry, 2022)
Copper(I) is an essential metal for all life forms. Though Cu(II) is the most abundant and stable state, its reduction to Cu(I) via an unclear mechanism is prerequisite for its bioutilization. In eukaryotes, the copper transporter-1(CTR1) is the primary high-affinity copper importer, although its mechanism and role in Cu(II) reduction remain uncharacterized. Here we show that extracellular amino-terminus of human CTR1 contains two methionine-histidine clusters and neighboring aspartates that distinctly bind Cu(I) and Cu(II) preceding its import. We determined that hCTR1 localizes at the basolateral membrane of polarized MDCK-II cells and that its endocytosis to Common-Recycling-Endosomes is regulated by reduction of Cu(II) to Cu(I) and subsequent Cu(I) coordination by the methionine cluster. We demonstrate the transient binding of both Cu(II) and Cu(I) during the reduction process is facilitated by aspartates that also act as another crucial determinant of hCTR1 endocytosis. Mutating the first Methionine cluster ((7)Met-Gly-Met(9)) and Asp(13)( )abrogated copper uptake and endocytosis upon copper treatment. This phenotype could be reverted by treating the cells with reduced and nonreoxidizable Cu(I). We show that histidine clusters, on other hand, bind Cu(II) and are crucial for hCTR1 functioning at limiting copper. Finally, we show that two N-terminal His-Met-Asp clusters exhibit functional complementarity, as the second cluster is sufficient to preserve copper-induced CTR1 endocytosis upon complete deletion of the first cluster. We propose a novel and detailed mechanism by which the two His-Met-Asp residues of hCTR1 amino-terminus not only bind copper, but also maintain its reduced state, crucial for intracellular uptake.